KAJIAN LITERATUR MENGENAI KESIAPAN MENIKAH PADA REMAJA YANG MENIKAH DINI - Qisty Adzillah; Tetti Solehati; Furkon Nurhakim (Jurnal Keperawatan Widya Gantari Indonesia, 2026)
Early marriage remains a serious challenge in many countries, including Indonesia, with a relatively high prevalence and multidimensional impacts on adolescent life. This phenomenon implies low marital readiness among adolescents across educational, economic, reproductive health, psychological, and social dimensions. This study aims to evaluate marital readiness among early-married adolescents through a systematic literature review. A literature search was conducted using the Population, Concept, Context (PCC) approach across PubMed, Scopus, ScienceDirect, and EBSCOhost databases, using the keywords "adolescent", "marital readiness", and "early marriage". The article selection process was visualized using a PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flow diagram, illustrating the stages of identification, screening, eligibility assessment, and inclusion in a systematic and transparent manner. Articles published between 2020 and 2025 were selected based on inclusion criteria, resulting in nine articles that were analyzed using the JBI Critical Appraisal tool. The review findings indicate that early marriage negatively affects nearly all dimensions of marital readiness. Adolescents who marry early are more vulnerable to school dropout, economic insecurity, reproductive complications, psychological issues such as depression and stress, as well as limitations in social relationships and household decision-making. These findings affirm that marital readiness is a multidimensional concept requiring holistic intervention. Future research is recommended to employ longitudinal designs, develop culturally contextualized marital readiness instruments suited to the Indonesian context, and include male adolescents to provide a more comprehensive picture.